Association of serum procalcitonin with the risk of coronary artery disease (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
IntroductionProcalcitonin (PCT), a calcitonin precursor is awell established novel systemic inflammatory biomarker.Inflammation in body plays important key role in pathogenesis of coronary artery disease (CAD). Inprevious studies, the results shows that the increase in PCT level have strong association with the severityof atherosclerosis, which leads to increase the risk of coronary artery disease (CAD) in the patients.Various studies have been done to investigate the role of PCT in the pathogenesis and risk of CAD,yet theirresults have been inconsistent. So, in the current study we evaluate the correlation between the serumprocalcitonin levels and risk of CAD.Aims and Objectives: The aim of the study was to find the association between the serum procalcitoninlevels and risk of coronary artery disease.Materials and Methods: 100 patients selected for the study, after taken the written consent form thepatients were equally divided into two group's case and control group. In case group 50 patients withangiographically proven CAD as case group and 50 apparently healthy age and sex matched adults ascontrol group. Serum procalcitonin levels were measured in both the groups using ELISA based kits.Results: Levels of Serum procalcitonin were 252.52 ± 17.43 ng/ml in case group as compared to 40.84 ±15.6 ng/ml in control group and their difference was statistically significant (p < 0.0001).Conclusion: The results of our study shows that there was strong relation between serum procalcitoninlevels and coronary artery disease risk.